AN OBSERVATIONAL STUDY OF DRUG UTILISATION PATTERN AND PHARMACOVIGILANCE OF ANTIPSYCHOTICS - R., Balaji; M., Sekkizhar; M., Asok Kumar; P., Nirmala (International Journal of Current Pharmaceutical Research, 2017)
Objective: Drug Utilization Research (DUR) was defined by the WHO in 1977 as The marketing, distribution, prescription, and use of drugs in a society, with special emphasis on the resulting medical, social and economic implicationsâ€. The main aim of conducting drug utilisation research is to facilitate rational use of drugs I,e the prescription of a well documented drug together with correct information at an affordable cost. Psychiatric disorders form an important public health priority among which psychotic disorders are the chief contributors to disability adjusted life years [DALYs] and are associated with high levels of health service utilization and treatment cost. Without the knowledge of how drugs are being prescribed and used it is difficult to initiate a discussion on rational drug use or to suggest measures to improve prescribing patterns. To analyse the drug utilization pattern by using standard parameters. Methods: After getting approval from the institutional human ethics committee and consent from the patients willing to participate in this study, a total of 79 prescriptions containing atleast one antipsychotic drug was collected in one year period from patients attending psychiatric OPD. The patients were given a one month follow up and the adverse effects which arise out of therapy are noted and analysed. Results: Out of the 79 participants, 59.49% were males and 40.51% were females. Regarding the morbidity distribution, Schizophrenia contributes to 50.63% and bipolar disorder contributes to 29.11% of diagnosis. Based on the analysis by WHO/INRUD standard guidelines, the average number of drugs and antipsychotic drugs per prescription were 3.32 and 1.38 respectively. The utilsation of antipsychotic drugs assessed by PDD/DDD ratio is equal to one for haloperidol and aripiprazole while it is less than one for other antipsychotic drugs. The adverse effects commonly encountered while treating psychotic cases are sedation, extra pyramidal symptoms, weight gain and anticholinergic side effects like constipation and urinary retention. Conclusion: The age and morbidity distribution of the participants are similar to the outcomes of many studies. The antipsychotic drugs haloperidol and aripiprazole are utilised appropriately while there is under utilisation of other antipsychotics. The volume of use of haloperidol, olanzapine benzodiazepines should be judicious considering their adverse effects.